TRANSFORMASI PENDIDIKAN ISLAM PERSPEKTIF HUKUM TIGA TAHAP AUGUSTE COMTE - Hamdan Adib (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2021)
This study aims to examine the transformation of Islamic education in terms of Auguste Comte's three-stage law. This study uses a qualitative approach with the type of research is library research. The results of this study are that the theological stage occurred when the emergence of the first Islamic boarding school in the form of a Salaf Islamic Boarding School whose focus of study was only on theological aspects or aspects of life after death. then the metaphysical stage shows the use of reason to answer problems that occur in humans both at the theological level as well as worship and muamalah. then the positive stage where humans have considered scientific facts in solving Islamic problems, namely the emergence of offers of humanist meanings of Islam such as pluralism and Islamic archipelago. The emergence of Islamic higher education institutions has also become a forum for discussing scientific answers by academics who have professional qualifications and competencies.